Synergistic effect of pretreatment, packaging and cobalt-60 gamma irradiation on nutrition and shelf life of pine nuts - Iqtedar, Mehwish; Wasim, Myra; Abdullah, Roheena; Kaleem, Afshan; Aihetasham, Ayesha; Chaudhary, Asma; Naz, Shagufta (Progress in Nutrition, 2019)
Pakistan is among the major producers of pine nuts but its export value is low which is attributed towards prevailing poor post-harvest conditions such as improper handling and storage and unhygienic conditions from field to the market. In this context, the present study was designed to evaluate the combinatorial effect of pretreatment, packaging and gamma irradiation on pine nut shelf life through evaluation of its microbial quality, sensory attributes and proximate analysis. Shelled pine nuts were pretreated (dried) under hygienic condition by two drying methods, solar drying (42ÅãC) and cabinet drying (55ÅãC). Two packaging strategies were undertaken in which samples were packed in inner aluminium and outer polythene packing whereas the other with only polythene packing. All the samples were irradiated with 7kGy radiation. Total bacterial load, Gram negative Enterobactereacae lactose and non-lactose fermenters and fungal count was observed in the range of log1 to none in all samples from initial till last day which showed the positive influence of drying treatment on samples. Insect infestation was not detected in any sample which showed that all combination of treatments were successful in eliminating the infestation. Oxidative stress when evaluated showed that oven dried control sample with aluminium and polythene packing showed high iodine value (78.8 mg.g-1) and low Thiobarbituric acid value (TBA) (0.006 mg.ml-1) whereas organoleptic properties showed good texture, colour and taste upto 20th day of storage. Conclusively, aluminium packing with polyethylene was effective with oven dried samples whereas if radiation is to be used then low dose with only polyethylene packing would be sufficient for long term preservation and to prevent post-harvest losses.